Revealing Strain Effects on the Chemical Composition of Perovskite Oxide Thin Films Surface, Bulk, and Interfaces - van den Bosch, Celeste A. M.; Cavallaro, Andrea; Moreno, Roberto; Cibin, Giannantonio; Kerherve, Gwilherm; Caicedo, José M.; Lippert, Thomas K.; Doebeli, Max; Santiso, José; Skinner, Stephen J.; Aguadero, Ainara (Advanced materials interfaces, 2020)
Understanding the effects of lattice strain on oxygen surface and diffusion kinetics in oxides is a controversial subject that is critical for developing efficient energy storage and conversion materials. In this work, high‐quality epitaxial thin films of the model perovskite La0.5Sr0.5Mn0.5Co0.5O3−δ (LSMC), under compressive or tensile strain, are characterized with a combination of in situ and ex situ bulk and surface‐sensitive techniques. The results demonstrate a nonlinear correlation of mechanical and chemical properties as a function of the operation conditions. It is observed that the effect of strain on reducibility is dependent on the “effective strain” induced on the chemical bonds. In‐plain strain, and in particular the relative BO length bond, is the key factor controlling which of the B‐site cation can be reduced preferentially. Furthermore, the need to use a set of complimentary techniques to isolate different chemically induced strain effects is proven. With this, it is confirmed that tensile strain favors the stabilization of a more reduced lattice, accompanied by greater segregation of strontium secondary phases and a decrease of oxygen exchange kinetics on LSMC thin films. La0.5Sr0.5Mn0.5Co0.5O3−δ strained epitaxial thin films are characterized using X‐ray diffraction, X‐ray absorption near edge spectroscopy and ion scattering techniques. The induced strain resulted in correlated structural and chemical changes with selectivity to the transition metal. In‐plain tensile strain promotes preferential reduction of Mn cations due to the higher Mn‐O/Ti‐O mismatch and favors a greater segregation of Sr secondary phases.